2008
DOI: 10.2340/16501977-0255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single botulinum toxin A injection to the external urethral sphincter for treating detrusor external sphincter dyssynergia in spinal cord injury

Abstract: This study demonstrates the effect of a single cystoscopic injection of botulinum toxin in detrusor external sphincter dyssynergia. Integrated electromyography is a good evaluation tool for the net effect and dosage of botulinum toxin. Patients with severe spasticity over the external urethral sphincter may require repeated injections or higher doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
1
20
1
1
Order By: Relevance
“…However, one study showed that sphincter activity became intermittent in patients with initially strong, continuous DSD, with a significant reduction in integrated EMG. 13 Our results showed that treatment outcome was related to the severity of DSD, with a strong correlation between PVR values before and after injection. Results in patients on urinary retention because of continuous DSD (type 3 in the Blaivas classification) were generally poor; only 20% had an excellent outcome (three out of 15 patients).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…However, one study showed that sphincter activity became intermittent in patients with initially strong, continuous DSD, with a significant reduction in integrated EMG. 13 Our results showed that treatment outcome was related to the severity of DSD, with a strong correlation between PVR values before and after injection. Results in patients on urinary retention because of continuous DSD (type 3 in the Blaivas classification) were generally poor; only 20% had an excellent outcome (three out of 15 patients).…”
Section: Discussionmentioning
confidence: 65%
“…AD is generally improved in most patients 4,5,7,8,13 but not all. 1 Change in voiding mode has been reported in most studies, and it is of clinical importance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Takođe je dokazan povoljan efekat tretmanom intramuskularnim injekcijama botulinskog toksina A cistoskopski u spoljašnji uretralni s nkter čime se smanjuje spasticitet i dissinergija s nktera mokraćne bešike. 13,17,18 Za smanjenje ekscitabilnosti detrusora mokraćne bešike vrlo su se e kasnim pokazali antiholinergici. 19 f) Za stimulaciju glatke muskulature mokraćne bešike koriste se eksponencijalne struje.…”
Section: Terapija Neurogene Disfunkcije Mokraćne Bešikeunclassified